Some features of roAp stars spectrum - Shavrina, A. V.; Polosukhina, N. S.; Tsymbal, V. V.; Pavlenko, Ya. V.; Yushchenko, A. V.; Gopka, V. F.; Veles, A. A. (Одеські астрономічні публікації, 2017)
We have shown the possibility for modelling Li blend6708 A, for two roAp stars, HD83368 and HD60435, taking into account lithium spots on the surfaces of these rotating stars. REE spots were also included in calculations. Slow rotating star HD101065 (Przybyslski’s star) give the possibility of scrupulous identification of REE lines blending Li line and estimation of 6Li/7Li ratio.